UTILITARIAN ANALYSIS OF THE ENFORCEMENT OF VILLAGE HEAD NEUTRALITY - Gede Ganesha; Ni Ketut Sari Adnyani; Ni Made Anggia Paramesthi Fajar; Komang Febrinayanti Dantes (Awang Long Law Review, 2026)
The 2024 Simultaneous Regional Election (Pilkada) emphasizes the importance of neutrality among village government officials, particularly village heads, in maintaining the integrity and fairness of the democratic process. The repeated violations of village head neutrality in Buleleng Regency, despite administrative sanctions, raise questions about the effectiveness of law enforcement. This study aims to analyze the enforcement of village head neutrality by Bawaslu Buleleng from a utilitarian perspective, focusing on social benefits and deterrent effects. The research uses a qualitative normative approach with a statute approach, examining relevant regulations, Bawaslu documents, and academic literature. The results indicate that Bawaslu has carried out its supervisory functions according to regulations through report receipt, verification, clarification, and administrative sanction recommendations. However, the effectiveness of these sanctions is limited, as repeated violations continue to occur. From a utilitarian perspective, sanctions limited to written warnings have not maximized social benefits, such as increased public trust and fair political competition. Enforcement of village head neutrality would be more effective if combined with deterrent sanctions, political education, and legal awareness campaigns. These findings are important for strengthening election supervision strategies and enhancing local democratic quality.